2016
DOI: 10.5089/9781484382349.001
|View full text |Cite
|
Sign up to set email alerts
|

Inequality, Gender Gaps and Economic Growth: Comparative Evidence for Sub-Saharan Africa

Abstract: A growing body of empirical evidence suggests that inequality-income or gender related-can impede economic growth. Using dynamic panel regressions and new time series data, this paper finds that both income and gender inequalities, including from legal gender-based restrictions, are jointly negatively associated with per capita GDP growth. Examining the relationship for countries at different stages of development, we find that this effect prevails mainly in lower income countries. In particular, per capita in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 23 publications
2
39
0
2
Order By: Relevance
“…(World Bank, 2006: 2) Similar statements have been made (more recently) by the IMF (e.g. Lagarde, 2016;Hakura et al 2016), the UN, ILO, or the OECD (e.g. OECD, ILO, IMF, and World Bank, 2014).…”
Section: Introductionmentioning
confidence: 55%
“…(World Bank, 2006: 2) Similar statements have been made (more recently) by the IMF (e.g. Lagarde, 2016;Hakura et al 2016), the UN, ILO, or the OECD (e.g. OECD, ILO, IMF, and World Bank, 2014).…”
Section: Introductionmentioning
confidence: 55%
“…The increase in the quantity of education and employment of women was shown to broaden the available talent pool in an economy, increase the income of women, and produce GDP growth [30]. Similarly, other studies indicated that the gender inequality in education reduces the average amount of human capital in a society and, therefore, harms economic growth [9,15,18,19,21,24,31].…”
Section: Economic Growth and Access Of Women To Educationmentioning
confidence: 99%
“…Gender differences in education were thought to lead automatically to gender differences in employment, particularly in the formal sector, where the employers would prefer workers with good training and, therefore, would not consider applications from women without education [9,24]. Conversely, if large barriers exist for women to access employment, the parents might decide that educating girls is not sufficiently lucrative and beneficial for the family, thereby producing a lower educational demand for women, resulting in a greater gender gap in education.…”
Section: Economic Growth and The Female Labor Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Inequality is measured by the Gini, a metric calculated and published by the Standardized World Income Inequality Database (SWIID; Solt, 2016). This variable is widely used in empirical studies as a measure of income inequality (see, for instance, Hakura, Hussain, Newiak, Thakoor, & Yang, 2016). The main advantage of the SWIID is that it provides broadest country coverage by incorporating a number of data sources to maximise the comparability over time.…”
Section: Economic Variablesmentioning
confidence: 99%